1999
DOI: 10.1063/1.869958
|View full text |Cite
|
Sign up to set email alerts
|

A numerical revisit of backward-facing step flow problem

Abstract: In the present study we take a fresh look at a laminar flow evolving into a larger channel through a step configured in a backward-facing format. We conduct steady three-dimensional Navier–Stokes flow analysis in the channel using the step geometry and flow conditions reported by Armaly et al. This allows a direct comparison with the results of physical experiments, thus serving to validate the numerical results computed in the range of 100⩽Re⩽1000. Results show that there is generally excellent agreement betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 16 publications
5
46
0
1
Order By: Relevance
“…From Figure 8, it is found that there exists no flow reattachment on the cavity bottom when x = 0.5. Then, no data in the cases at 0.5 of the molar ratio are plotted Chiang and Sheu 17) reported results of three-dimensional numerical computations for a backward-facing Newtonian fluid flow. They changed the aspect ratio from 2 to 100.…”
Section: Rheological Characteristicsmentioning
confidence: 99%
“…From Figure 8, it is found that there exists no flow reattachment on the cavity bottom when x = 0.5. Then, no data in the cases at 0.5 of the molar ratio are plotted Chiang and Sheu 17) reported results of three-dimensional numerical computations for a backward-facing Newtonian fluid flow. They changed the aspect ratio from 2 to 100.…”
Section: Rheological Characteristicsmentioning
confidence: 99%
“…It represents a standard test for investigating the flow separation and reattachment. It has been already used by numerous researchers as a benchmark test for various numerical methods [19][20][21][22][23][24][25]. The domain of the problem is characterized by a planar channel with sudden change of the geometry (Figure 1), which governs the flow separation, and generation of several re-circulating zones downward the step, described by positions   1 2 3 , ,…”
Section: Problem Definitionmentioning
confidence: 99%
“…The well-known Backward-Facing Step problem [19][20][21][22][23][24][25] (BFS) is considered since its solution is well coped with in the literature, and is at the same time complex enough to challenge the proposed numerical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[2,5,6,9,10,11,12,13,14,15]). Armaly et al [2] performed Laser-Doppler measurements of velocity distribution and reattachment length downstream of a BFS mounted in a 18:1 aspect ratio (step span/step height) channel for a wide range of Reynolds number, 70 < Re < 8000.…”
Section: Introductionmentioning
confidence: 99%